Anti-mycobacterial haliclonadiamine alkaloids from the Okinawan marine sponge Haliclona sp. collected at Iriomote Island. (August 2018) - Abdjul, Delfly B.; Yagi, Akiho; Yamazaki, Hiroyuki; Kirikoshi, Ryota; Takahashi, Ohgi; Namikoshi, Michio; Uchida, Ryuji
Graphical abstract: Highlights: Two new halichondriamine derivatives were isolated from an Okinawan marine sponge Haliclona sp. The structures of the new alkaloids were elucidated based on their NMR spectra. These new compounds showed anti- Mycobacterium avium complex (MAC) activity. Abstract: Two new haliclonadiamine derivatives, halichondriamine C (1 ) and 1- epi -halichondriamine C (2 ), were isolated from the Okinawan marine sponge Haliclona sp. together with known haliclonadiamine (3 ) and papuamine (4 ). The structures of 1 and 2 were elucidated based on their spectroscopic data by comparisons with those for related compounds. Compounds 1 and 2 were epimers of each other at the C-1 position. Compounds 1 –4 inhibited the growth of Mycobacterium smegmatis and M. bovis BCG and exhibited antibacterial activities against M. avium and M. intracellulare as pathogens of M. avium complex (MAC) disease.